Rancang Bangun Evaporator Ultrasonik Untuk Produk Sari Kurma yang Bekerja Pada Suhu Rendah - Hendrawan, iyus; Haifan, Mohamad (JTM-ITI (Jurnal Teknik Mesin ITI), 2017)
Palm juice is a supplementary foodÂ  resulting from the extraction / pressing the palm fruit into a viscous liquid that is ready to be consumed. Nutrient content and nutritional no different with dates. On the small scale industries, palm juice processing is done through the process of evaporation at high temperature, consequently some important compounds such as vitamins and minerals will be damage, so that the benefits of palm juice for health will decrease. Ultrasonic technology is one method that can be applied to the process of evaporation combined with low temperatures, so that the product obtained palm juice is safe and does not lead to degradation of the important compounds it contains. The research objective is to design and test wake evaporator working under ultrasonic combined with low temperatures to evaporate the water content in the palm juice. Results of ultrasonic evaporator design has a dimension of 41 cm in high, 26 cm diameter and processing chamber capacity is 13 liters. In general, the results of design and test electronic evaporator goes well. From the test results for the evaporation of water (without a date palm juice) recorded water evaporation rate of 275 ml / h, while the water in the palm juiceÂ  carrying water evaporation rate of 87.5 ml / hr. In addition to palm juice evaporation, ultrasonic evaporator can be used for evaporative other foodstuffs as well as other food processes, such as pasteurization and sterilization of milk, incubation yougurt etc.